Geo-Informatics in Resource Management and Sustainable Ecosystem Third International Conference, GRMSE 2015, Wuhan, China, October 16-18, 2015, Revised Selected Papers - Bian, Fuling; Xie, Yichun (Communications in Computer and Information Science,, 2016)
This volume constitutes the refereed proceedings of the Third International Conference on Geo-Informatics in Resource Management and Sustainable Ecosystem, GRMSE 2015, held in Wuhan, China, in October 2015. The 101 papers presented were carefully reviewed and selected from 321 submissions. The papers are divided into topical sections on Smart City in Resource Management and Sustainable Ecosystem; Spatial Data Acquisition Through RS and GIS in Resource Management and Sustainable Ecosystem; Ecological and Environmental Data Processing and Management; Advanced Geospatial Model and Analysis for Understanding Ecological and Environmental Process; Applications of Geo-Informatics in Resource Management and Sustainable Ecosystem.